Managing data with Microsoft Excel - Carlberg, Conrad George (Business solutions., 2004)
You have learned the methods to the madness of Excel. Formulas and functions are friends instead of foes. Yet you know there's something missing that could make your job even easier. That "something" is efficient and effective data management. Managing Data with Excel is the only book on the market that focuses on just that. Learn how to efficiently move data, automate data storage and import data into worksheets and pivot tables. Case studies are included in each chapter to illustrate real-world applications of these functions. Invest your time in learning this now so that you can stop wasting your time figuring out how to work around problems.